Perubahan Kurikulum Pendidikan Agama Islam - Ninda Akilla; Rani Saputri; Muhammad Fadli; Wama Fima; Mustafiyanti Mustafiyanti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Curriculum development is the most important part in improving the quality of learning. The development of this curriculum is very important to increase the success of the education system as a whole because the curriculum is a factor in improving the quality of education. Along with the development of science and technology the government always makes various improvement and efforts and improvement to the curriculum or material in educational programs. Data collection techniques used were interviews, observation and documentation with data reduction analysis methods, data presentation and drawing conclusions.involved in the preparation and development of the curriculum are: (a) Madrasah supervisor (b) Committee (c) Headmaster (d) Teacher as a learning driver, guiding.